2020
DOI: 10.1186/s12894-020-00716-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinicopathologic parameters and oncologic outcomes between type 1 and type 2 papillary renal cell carcinoma

Abstract: Background To compare the clinicopathologic parameters and oncologic outcomes between type 1 and type 2 papillary renal cell carcinoma (PRCC). Methods This study was approved by the review board (NO.XYFY2019-KL032–01). Between 2007 and 2018, 52 consecutive patients who underwent surgery at a single tertiary referral hospital were included. Clinicopathologic and survival data were collected and entered into a database. The Kaplan-Meier method, and univariate and multivariate Cox proportional hazard regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
6
9
0
Order By: Relevance
“…Some previous studies have demonstrated that type 2 pRCC was associated with worse survival than type 1 (3,13,25,29). However, the conclusion must be taken with caution, as these studies may be limited by sample size, short duration of follow-up, or the infrequency of death related to pRCC (25,26).…”
Section: Discussionmentioning
confidence: 95%
“…Some previous studies have demonstrated that type 2 pRCC was associated with worse survival than type 1 (3,13,25,29). However, the conclusion must be taken with caution, as these studies may be limited by sample size, short duration of follow-up, or the infrequency of death related to pRCC (25,26).…”
Section: Discussionmentioning
confidence: 95%
“…PRCC type 2 has a more advanced stage, a higher nuclear grade, and a worse prognosis than type 1 (4-6). However, on the contrary, some studies reported that PRCC subtyping had no effect on oncologic outcomes (7)(8)(9)(10). Therefore, whether the histologic subtypes affect the prognosis are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary renal cell carcinoma (PRCC) is the second most frequent type of renal cell carcinoma (RCC) after clear cell RCC. It accounts for 6-18% of all RCC cases [ 10 ].…”
Section: Discussionmentioning
confidence: 99%